37 Performance, Health, and Physiological Responses of Feedlot Cattle Supplemented with Pre- and Probiotic Ingredients. (8th March 2022) - Mackey, Shea; Cooke, Reinaldo F; Colombo, Eduardo; Pickett, Autumn; Batista, Luis Fernando; Block, Elliot; Brandão, Alice
Abstract: This experiment compared performance and health responses of feedlot cattle receiving a ymbiotic supplement, which replaced or was fed in conjunction with feed-grade antimicrobials. Angus-influenced steers (n = 192) from 4 different sources were weaned and immediately transported for 800 km. Steers arrived at the experimental feedlot on d 0, and a shrunk body weight (BW) was immediately recorded. Steers were ranked by source and shrunk BW, and allocated to 1 of 24 drylot pens (8 steers/pen). Pens received a free-choice diet containing: 1) monensin and tylosin (RT; 360 mg/steer daily from Rumensin and 90 mg/steer daily from Tylan; Elanco Animal Health, Greenfield, IN), 2) yeast-derived ingredient and B. subtilis probiotic (CC; 18 g/steer daily of Celmanax and 28 g/steer daily of Certillus; Church and Dwight Co., Inc., Princeton, NJ), or 3) combination of RT and CC (RTCC). Cattle were slaughtered according to BW, and slaughter groups were balanced by treatments (33 steers on d 200, 33 steers on d 230, 63 steers on d 257, and 63 head on d 285). Feed intake during the experimental period (d 0 to slaughter) was greater (P < 0.01) in CC compared to RT and RTCC, although feed efficiency was lower in CC (P = 0.02). No treatment effects were observed for BW gain (P = 0.61), final BW (P = 0.67), or morbidity (P = 0.15). Upon slaughter, CC had higher marbling scores compared to RT (P = 0.04). Both CC and RTCC had larger Longissimus muscle area (P = 0.07) and more carcasses grading choice or better (P < 0.01) than RT. Liver abscesses tended (P ≤ 0.09) to be greater in CC compared to RTCC and RT. Hot carcass weight, dressing percentage, backfat thickness, and yield grade did not differ among treatments (P ≥ 0.20). Collectively, replacing RT with CC improved feed intake and certain carcass measures despite decreased feed efficiency, whereas combining CC with RT did not yield additional performance and health benefits.